Disease-Induced Changes in Salivary Gland Function and the Composition of Saliva. (October 2021) - Proctor, G.B.; Shaalan, A.M.
Although the physiological control of salivary secretion has been well studied, the impact of disease on salivary gland function and how this changes the composition and function of saliva is less well understood and is considered in this review. Secretion of saliva is dependent upon nerve-mediated stimuli, which activate glandular fluid and protein secretory mechanisms. The volume of saliva secreted by salivary glands depends upon the frequency and intensity of nerve-mediated stimuli, which increase dramatically with food intake and are subject to facilitatory or inhibitory influences within the central nervous system. Longer-term changes in saliva secretion have been found to occur in response to dietary change and aging, and these physiological influences can alter the composition and function of saliva in the mouth. Salivary gland dysfunction is associated with different diseases, including Sjögren syndrome, sialadenitis, and iatrogenic disease, due to radiotherapy and medications and is usually reported as a loss of secretory volume, which can range in severity. Defining salivary gland dysfunction by measuring salivary flow rates can be difficult since these vary widely in the healthy population. However, saliva can be sampled noninvasively and repeatedly, which facilitates longitudinal studies of subjects, providing a clearer picture of altered function. The application of omics technologies has revealed changes in saliva composition in many systemic diseases, offering disease biomarkers, but these compositional changes may not be related to salivary gland dysfunction. In Sjögren syndrome, there appears to be a change in the rheology of saliva due to altered mucin glycosylation. Analysis of glandular saliva in diseases or therapeutic interventions causing salivary gland inflammation frequently shows increased electrolyte concentrations and increased presence of innate immune proteins, most notably lactoferrin. Altering nerve-mediated signaling of salivary gland secretion contributes to medication-induced dysfunction and may also contribute to altered saliva composition in neurodegenerative disease.